Molecular Engineering of Laser‐Induced Graphene for Potential‐Driven Broad‐Spectrum Antimicrobial and Antiviral Applications. Issue 51 (20th October 2021) - Gu, Meijia; Huang, Libei; Wang, Zhaoyu; Guo, Weihua; Cheng, Le; Yuan, Yuncong; Zhou, Zhou; Hu, Liu; Chen, Sijie; Shen, Chao; Tang, Ben Zhong; Ye, Ruquan
Abstract: Worldwide, countless deaths have been caused by the coronavirus disease 2019. In addition to the virus variants, an increasing number of fatal fungal infections have been reported, which further exacerbates the scenario. Therefore, the development of porous surfaces with both antiviral and antimicrobial capacities is of urgent need. Here, a cost‐effective, nontoxic, and metal‐free strategy is reported for the surface engineering of laser‐induced graphene (LIG). The authors covalently engineer the surface potential of the LIG from −14 to ≈+35 mV (LIG + ), enabling both high‐efficiency antimicrobial and antiviral performance under mild conditions. Specifically, several candidate microorganisms of different types, including Escherichia coli, Streptomyces tenebrarius, and Candida albicans, are almost completely inactivated after 10‐min solar irradiation. LIG + also exhibits a strong antiviral effect against human coronaviruses: 99% HCoV‐OC43 and 100% HCoV‐229E inactivation are achieved after 20‐min treatment. Such enhancement may also be observed against other types of pathogens that are heat‐sensitive and oppositely charged. Besides, the covalent modification strategy alleviates the leaching problem, and the low cytotoxicity of LIG + makes it advantageous. This study highlights the synergy of surface potential and photothermal effect in the inactivation of pathogens and it provides a direction for designing porous materials for airborne disease removal and water disinfection. Abstract : Chemical modification of laser‐induced graphene with quaternary pyridinium inverts surface potential, which enables both broad‐spectrum antimicrobial (≈100% for bacteria and fungi) and antiviral (≈100% for the human coronavirus HCoV‐229E) activities from the synergy of photothermal effect and electrostatic interactions.